«The Crisis of Democratic Representation, with a final reflection about the crisis old and new elements» - Freire, A. (WORKSHOP «THE CRISIS AND THE CHALLENGES OF DEMOCRACY», CES-UC, Coimbra, November 4-6, 2019, 2019)
André Freire (2019), como keynote speaker e participante no WORKSHOP «THE CRISIS AND THE CHALLENGES OF DEMOCRACY», CES-UC, Coimbra, November 4-6, 2019, nomeadamente para a apresentar uma comunicação («The Crisis of Democratic Representation, with a final reflection about the crisis old and new elements») e discutir papers apresentados por outros no segundo dia (5-11-2019).